Finite Element Analysis of Novel Separable Fixture for Easy Retrievement in Case with Peri-Implantitis - Kim, Won Hyeon (Materials (Basel), 2019)
Peri-implantitis is a common complication following dental implant placement, which may lead to bone loss and fixation failure. With the conventional fixture, it is difficult to perfectly clear-up the infection. To solve this, we have designed a separable fixture of which the top part is replaceable. This study aimed to compare the structural and biomechanical stability of the separable and conventional fixture. A single surgical model corresponding to the first molar in a virtual mandible model and conventional/separable implants were reproduced to compare the biomechanical characteristics of the implants using finite element analysis (FEA). The loading condition was 200N preload in the first step, and 100N (Axial), 100N (15°), and 30N (45°) in the second step. The stress distribution on the cortical bone in the separable implant was lower than the conventional implant. In particular, the Peak von Mises Stress (PVMS) values of the separable implant under lateral load was found to be about twice as low as that of the conventional implant. In this study, we suggest that the separable implant has an equivalent biomechanical stability compared to the conventional implant, is easy to retrieve in the case of peri-implantitis, and has an excellent initial stability after the surgery when used in stage 2.